2023
DOI: 10.1002/adhm.202203080
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐Targeting Near‐Infrared Dimeric Heptamethine Cyanine Photosensitizers with an Aromatic Diphenol Linker for Imaging‐Guided Cancer Phototherapy

Abstract: Phototherapy is considered a promising alternative to conventional tumor treatments due to its noninvasive modality and effective therapeutic effect. However, designing a photosensitizer with satisfactory therapeutic effect and high security remains a considerable challenge. Herein, a series of dimeric heptamethine cyanine photosensitizers with an aromatic diphenol linker at the meso position is developed to improve the photothermal conversion efficiency (PCE). Thanks to the extended conjugate system and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…According to Fig. S8 (ESI †), the photothermal conversion efficiency of the Flav7@DSPE-PEGG NPs was 37.21%, which is a fairly good value among organic small molecule PTAs, [32][33][34][35][36] such as cyanine, porphyrin, and BODIPY/aza-BODIPY dyes (Table S1, ESI †). These results demonstrated good photothermal properties upon NIR laser irradiation and suggested that the Flav7@DSPE-PEGG NPs could be used as an efficient PTA for photothermal treatment.…”
Section: Photothermal Performance Of the Flav7@dspe-pegg Npsmentioning
confidence: 99%
“…According to Fig. S8 (ESI †), the photothermal conversion efficiency of the Flav7@DSPE-PEGG NPs was 37.21%, which is a fairly good value among organic small molecule PTAs, [32][33][34][35][36] such as cyanine, porphyrin, and BODIPY/aza-BODIPY dyes (Table S1, ESI †). These results demonstrated good photothermal properties upon NIR laser irradiation and suggested that the Flav7@DSPE-PEGG NPs could be used as an efficient PTA for photothermal treatment.…”
Section: Photothermal Performance Of the Flav7@dspe-pegg Npsmentioning
confidence: 99%
“…A few strategies have been proposed for improving the performance of heptamethine cyanine dyes as photosensitizers for effective tumour phototherapy. For example, structural modifications of the dye backbone offered opportunities to enhance the photostability and improve the optical properties, 21,22 and developing carrier systems loading the dyes helped to ameliorate the pharmacokinetics. 23,24 However, altering the backbone structure has risks to diminish the intrinsic tumour-targeting ability of these dyes, since the structure-activity relationship of the tumourtargeting ability has not been clarified yet, 25 and encapsulating the dyes into delivery systems would mask the dye-mediated tumourtargeting.…”
Section: Nanoscale Horizonsmentioning
confidence: 99%
“…As commonly acknowledged, certain heptamethine cyanine dyes have already demonstrated an exceptional ability to specifically target tumor mitochondria. In addition, the combination of mitochondria-targeting agents with TMX could potentially reduce the required dosage of TMX for inducing mitochondria dysfunction. , Consequently, utilizing heptamethine cyanine dye to conjugate with TMX may serve as a promising approach for photodynamic immunotherapy by effectively suppressing PD-L1 and TGF-β, both acting as antitumor and cotherapy agents. , To validate this hypothesis, we developed an MHI-TMX chemical compound by combining a mitochondria-targeted heptamethine cyanine PDT-dye called MHI with TMX, an agent that inhibits mitochondrial complex I, which was further assembled with albumin (ALB) to create MHI-TMX@ALB nanoparticles (Scheme ). By employing this approach, MHI-TMX@ALB nanoparticles specifically accumulated in tumors and suppressed the expression of PD-L1 and TGF-β.…”
Section: Introductionmentioning
confidence: 99%